A novel approach in treating diabetic foot ulcer with hyperbaric oxygen therapy: a case report - Zainal, Mohd Syazwan; Ghazali, Khairul Azmi; Mohamad Nor, Masdiamin; Devaraj, Navin Kumar; S., Rampal (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Diabetes mellitus has reached epidemic levels in Malaysia due to increase in its risk factors such as obesity, dietary and sedentary lifestyle. In patients with uncontrolled diabetes mellitus, diabetic foot ulcer (DFU)is a common complication. Managing diabetic foot infection is often multifactorial and intricate. The management DFU demands multi-speciality approach and often tedious. Hyperbaric oxygen therapy (HBOT) is a promising adjunctive treatment used to enhance the healing process plus reduces cost and recovery time. This is a case of a 52 years old lady, with underlying poorly diabetes mellitus, who presented with diabetic foot ulcer Wagner IV classification in sepsis. She underwent trans-metatarsal amputation followed by split skin grafting with additional adjunctive HBOT in a tertiary hospital.